VDTA Based Transadmittance Mode Instrumentation Amplifier with Experimental results - Raj, Niranjan; Dutta, Somenath; Ranjan, Rajeev Kumar; Singh, Dharmendra Kumar; Kuntman, Hakan (Research Square Platform LLC, 2023)
Abstract A Voltage Differencing Transconductance Amplifier (VDTA) based trans-admittance mode (TAM) instrumentation amplifier (IA) has been proposed in this article. Proposed IA provides electronically tunable gain with biasing current along with high bandwidth (BW) and CMRR. In addition, the proposed IA does not need any resistor matching. An offset of the presented amplifier circuit can be suppressed using an integrator feedback stage. The functional verification is performed using 0.18 µm TSMC process parameter. Monte Carlo Sampling (MCS) is carried out, thus proving robustness of the circuit. As an application part, a noisy ECG signal is applied to get a clean amplified signal. A CMRR of 131dB-146.8 dB has been obtained depending on different values of the components, and biasing conditions. 30 MHz bandwidth is obtained for the proposed IA. The IA layout required 80 × 49 µm2 areas. The experimental verification has been done using commercially available ICs CA3080.